Speed Control Turbin Pada Pembangkit Listrik Micro Hydro Pintu Air Bendungan - Permana Sitanggang, Doni (Riset Sinergi Indonesia (RISINDO), 2022)
This thesis aims to develop a new technology in the field of control system speed control on the dam-based microcontroller. Where the workings of this tool is utilizing Sensor water level to enable the water when the water has already reached the maximum limit. And utilize the Buzzer as a marker that the water has already reached the limit, and harness the power window motor as the drive to open the floodgates. And utilizing a dc motor as a speed control. And use the database as a data storage. With the establishment of this system, people are expected to be more efficient in the utilization of the dam.